EFFECT OF SALINITY OF CONCENTRATION OF POLYMER SOLUTION ON VISCOSITY - MOHD ZULKIFLI, MUHAMAD SYAHMI (UNIVERSITI TEKNOLOGI PETRONAS, 2013)
Polymers are widely used in oil and gas industries such as in polymer flooding in Enhanced Oil Recovery (EOR). In field, polymer solution is made by mixing polymer powder with brine. However, polymers are very sensitive towards salinity of brine. High salinity can affect the viscosity of polymer solution. The objectives of this research are to measure the rheological properties of Xanthan gum and HPAM solution as a function of shear rate, polymer concentration, salinity and to justify the relationship of the above variables which affecting the viscosity of polymers solutions. The methodology used in this research is experimental methods. Several experiments will be done to verify the effect of salinity, shear rate and polymer concentration on polymer solution viscosity. Polymer solutions will be prepared by using Xanthan gum and HPAM with different concentration ranging from 500 ppm until 2500 ppm. Each sample will be prepared by mixing with different salinity of brine (NaCl, CaCl2 and MgCl2). Viscosities of all these samples will be measured by using dial viscometer Fann 35A and digital LV Brookfield viscometer at 25°C (77°F). This project had been done conducted at Scomi GRTC, Shah Alam by using their chemicals, equipments and tools. In conclusion, the finding of this project is Xanthan gum yield higher viscosities as a function of polymer concentration compared to HPAM solution. Still, both of polymers show increasing trending. Then, both polymers solution viscosity are affected by the salinity of brines and as well as type of salt (monovalent or divalent). Both of polymer solutions exhibit the non-Newtonian fluids, which are dependent on shear rate.